Strategi Kepala Sekolah dalam Membangun Gaya Hidup Religius di Sekolah - Ais Zakiyudin (Universitas Bina Sarana Informatika, 2020)
Abstract - This study aims to find out, (1) the principal's strategy in building a religious lifestyle for their students, (2) an activity program that directs students to have a religious lifestyle, (3) how to introduce a religious lifestyle and the importance of implementation. a religious lifestyle, (4) the support of teachers and parents of students in implementing a religious lifestyle. This study uses a qualitative approach with case study research. The location of this research is the Integrated Islamic Elementary School (SDIT) Wirausaha Indonesia, Cikarang Utara, Bekasi Regency, West Java Province. Data collection techniques through interviews, observation and documentation. The analysis technique used is reduction, data display and data verification. The results of this study are (1) the principal's strategy in building a religious lifestyle for their students, the first step is a meeting with the curriculum team to create a lesson curriculum and activity program which is then socialized to the entire board of teachers, students and parents. , (2) program activities that can lead students to have a religious lifestyle, namely the Dhuha prayer in congregation, the Dhuhur prayer in congregation, Al-Qur'an learning activities and memorization, (3) how to introduce a religious lifestyle is through social media , websites, print and meetings, (4) how to build support for teachers and parents in adopting a religious lifestyle, namely by providing teachers with religious knowledge regularly during meetings and religious studies once a week, while parental support is by means of socialization massive on whatsapp groups, websites and other means.